Raising the issue of DNAR orders in vascular surgery patients. Issue 1 (8th February 2016) - McIntosh, Rachel; Webb, Hannah; Hartley, Matthew; Brooks, Marcus
Abstract: The Tracey Report has recently raised the status of Do Not Attempt Cardio Pulmonary Resuscitation (DNACPR) orders in the hospital setting.[1] Guidelines are in place both nationally and locally to provide advice to clinicians on when to discuss DNACPR, and the approach to be taken. There was concern that on a busy regional vascular surgery unit, discussion of resuscitation status was not regular practice. Consequently, some patients were at risk of being inappropriately resuscitated, particularly out of hours. The North Bristol Somerset and Gloucester DNAR decision tree[2] was the tool used to decide whether a patient should have a documented discussion and/or a DNACPR form completed. We correlated the outcome of the decision tree with the presence of a DNACPR form or documented resuscitation discussion. Baseline measurements from all vascular inpatients on the vascular surgery unit demonstrated that only 27% had a DNACPR form or documented discussion in concordance with the DNACPR Decision Tree outcome. The aim of this project was to increase the proportion of patients with concordance of the DNACPR decision tree outcome with documented discussion or DNACPR form. The following three simple interventions raised concordance from 27% to 64% of patients on the vascular surgery unit. 1. Including resuscitation status of each patient as a column in the doctors daily handover. 2. Posters in staff only areas to highlight the meaning of DNACPR and raise awareness of the DNACPR decision tree. 3. Educational meeting surrounding DNACPR with the vascular surgery consultants, led by a care of the elderly consultant . This project has highlighted how raising awareness around DNACPR increases discussion amongst the clinical team surrounding resuscitation status of a patient. Consequently, this enables discussion to be had with patient and their family.